Malignant syphilis in an immunocompetent female patient - Camila Bueno Requena; Cínthia Rosane Orasmo; Juliana Polizel Ocanha; Silvia Regina Catharino Sartore Barraviera; Mariangela Esther Alencar Marques; Silvio Alencar Marques (Sociedade Brasileira de Dermatologia, 2014)
Malignant syphilis is an uncommon manifestation of secondary syphilis, in which necrotic lesions may be associated with systemic signs and symptoms. Generally it occurs in an immunosuppressed patient, mainly HIV-infected, but might be observed on those who have normal immune response. Since there is an exponential increase in the number of syphilis cases, more diagnoses of malignant syphilis must be expected. We report a case in an immunocompetent female patient.